Migrated guidewire: an unusual cause for recurrent aural polyps - Liew, Kong Yew; Aun, Wee Chong (Wolters Kluwer Medknow Publications, 2017)
Aural polyps are secondary to multiple ear pathologies, most commonly inflammatory or cholesteatoma related. Here, we present a rare case of recurrent aural polyps caused by guidewire migration into the middle ear with serious systemic complications and our attempts at removal.